Landscape, Process and Power: Re-evaluating Traditional Environmental Knowledge - O’Brien, Colleen Marie (Ethnobiology Letters, 2010)
Review of Landscape, Process and Power: Re-evaluating Traditional Environmental Knowledge. Serena Heckler, ed. 2009. Berghahn Books, New York. Pp. 304, 21 illustrations, bibliography, index. 95.00 (hardback). ISBN 978-1-84545-549-1